NISO plus 2022 Miles Conrad lecture: The role of a library in a world of unstructured data - Brennan, Patricia Flatley (Information services & use, 2022)
Throughout its nearly two hundred year existence, the National Library of Medicine (NLM) (https://www.nlm.nih.gov/) has advanced biomedicine and public health by acquiring, organizing, preserving, and disseminating knowledge essential to health and medicine. NLM has devised many innovations including standard terminologies and messaging formats such as the Journal Article Tag Suite (https://dtd.nlm.nih.gov/) to organize and manage biomedical literature. While scientific communication largely relied on books and journals over the last two hundred years, digital data are quickly forming the substrate of scientific communications. Data come in forms with much less structure than that afforded by publications, and these can vary from observations made during carefully controlled clinical trials to streams of genomic sequences to the counts of footfalls captured by personal devices. Coincidently, an increasingly diverse set of users – from clinicians to laypeople to public health to big pharma to scientists – bring unique perspectives as they draw meaning from new sets of scientific output. How does a modern library meet its mission to acquire, organize, preserve, and disseminate the many outputs of contemporary science? What role do standards play? How does NLM help this diverse set of stakeholders derive meaning from its resources?